ANALYSIS OF VAK LEARNING STYLES (VISUAL, AUDITORIAL, KINESTHETIC) AND BIOLOGY LEARNING OUTCOMES ON PLANT TISSUE MATERIAL IN CLASS XI SCIENCE SMA NEGERI 1 BERINGIN TP 2023/2024 - Edi, Syahmi (Universitas Negeri Medan, 2024)
This research aims to determine the relationship between students' visual, auditory and kinesthetic learning styles with students' biology learning outcomes. The type of research used is descriptive research with a quantitative approach. In this study there were 71 people using a sampling technique, namely random sampling. The instruments used in data collection were questionnaires and tests. The research results showed that students in class XI Science at SMA Negeri 1 Beringin consisting of classes XI IPA 1 and IPA 2 tend to have a visual learning style with 41 students (57.75%), while students who have an auditory learning style are 16 people (22.54%), and students who have a kinesthetic learning style are 14 people (19.71%). This research shows that the visual learning style variable (X1) has rcount = 0.601 > rtable = 0.308, the auditory learning style variable (X2) having rcount = 0.536 > rtable = 0.497 and the kinesthetic learning style variable (X3) has rcount = 0.547 > rtable = 0.533. Based on the research results, it was concluded that student learning styles greatly influence students' biology learning outcomes.